The Effects of Walking Lunges and Adductor Stretching on the Flexibility of Volleyball-Specialization Students at Universitas Negeri Makassar (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effects of walking lunges and adductor stretching on the flexibility of Volleyball-Specialization students in the Sports Coaching Education Program, Faculty of Sports and Health Sciences, Universitas Negeri Makassar. The research employed an experimental method using a group pretest-posttest design. The sample consisted of 40 male students, divided into two treatment groups. The study was conducted at the Sports Campus of FIKK UNM. Flexibility measurements were taken before and after the intervention. The results indicate a significant effect of walking lunges training on improving flexibility, as shown by a t-value of 15.742 (p < 0.05). Adductor stretching also demonstrated a significant effect with a t-value of 10.767 (p < 0.05). Furthermore, comparative testing revealed a significant difference in the effects of the two training methods on flexibility, indicated by a t-value of 2.554 (p < 0.05). These findings suggest that both walking lunges and adductor stretching are effective in enhancing flexibility among Volleyball-Specialization students, with each exercise contributing differently to flexibility improvement.